Student Perceptions of Online Learning: Student Opinions and Expectations: Persepsi Mahasiswa Terhadap Pembelajaran Secara Online: Pendapat dan Harapan Mahasiswa - Ismunandar, Denni; Primadewi, Ardhin; Amalia, Sofri Rizka (Universitas Wiralodra, 2021)
The case of Covid-19 affects the world of education. One of the consequences is that learning to be carried out online is decided by the Indonesian government. However, in learning, this strategy is burdensome for learners. The goal of this case study is to find out student opinions on online applications are used, what their challenges are, and what online learning expectations of students are. This research uses a questionnaire to find out student opinions using a Google form. Ninety-two students from various universities were the number of respondents. To get results, the questionnaires that have been collected are evaluated manually. The outcome of this study is that most of the software used by lecturers was unable to enhance the comprehension of the content being learned by students. During this pandemic, the hope of students in learning is to increase discussion time and time to complete assignments, not too many assignments, and the strategy of the university to have internet quota buying subsidies